Genome Sequence of Bacillus alveayuensis Strain 24KAM51, a Halotolerant Thermophile Isolated from a Hydrothermal Vent - Filippidou, Sevasti; Wunderlin, Tina; Junier, Thomas; Jeanneret, Nicole; Johnson, Shannon; McMurry, Kim; Gleasner, Cheryl D.; Lo, Chien-Chi; Li, Po-E; Vuyisich, Momchilo; Chain, Patrick S.; Junier, Pilar (My University, 2015)
Bacillus alveayuensis strain 24KAM51 was isolated from a marine hydrothermal vent in Milos, Greece. Its genome depicts interesting features of halotolerance and resistance to heavy metals.